Heritage Conservation and Social Engagement - Peters, Renata F. (Book collections on Project MUSE., 2020)
Heritage Conservation and Social Engagement explores different kinds of engagement, participation, access, and creative use of resources motivated by the practice of conservation, and offers ethical and practical perspectives from which to approach cultural heritage projects.